1986
DOI: 10.1016/s0735-1097(86)80050-x
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic receptor properties of canine myocardium: Effects of chronic myocardial infarction

Abstract: To determine the effects of chronic myocardial infarction on beta-adrenergic properties of canine myocardium, the hearts of nine mongrel dogs were studied 3 weeks after acute myocardial infarction. Infarction was produced by ligating the left anterior descending coronary artery in five dogs and the circumflex artery in four dogs. The heart was divided into normal and infarct zones (either anterior or posterior, depending on the vessel ligated) and marginal zones (septal and lateral), each zone being subdivided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Exercise-induced increases in lymphocyte 8-adrenoceptor density are also impaired in humans with heart failure (77,153,155). Similar observations have been made in several experimental models of heart failure induced by occlusion of the coronary vessels as in the guinea pig (4,7) and the dog (60,125). A summary of these observations is provided in Table 7.…”
Section: @-A Drenoceptorssupporting
confidence: 64%
See 1 more Smart Citation
“…Exercise-induced increases in lymphocyte 8-adrenoceptor density are also impaired in humans with heart failure (77,153,155). Similar observations have been made in several experimental models of heart failure induced by occlusion of the coronary vessels as in the guinea pig (4,7) and the dog (60,125). A summary of these observations is provided in Table 7.…”
Section: @-A Drenoceptorssupporting
confidence: 64%
“…The coronary artery occlusion model, wherein initial ischemia is induced by limiting myocardial blood suppiy usually by ligation, has been successfully employed in a wide variety of species, notably the dog (47,125,172,174,186,222), guinea pig (7,145,148), cat (42), and the rat (53,105.193,244). Alternative experimental techniques include induction of myocardial stress by rapid electrical pacing of the heart and pressure or volume overload by obstruction of arterial or venous blood flow (9 1,104,122,139,199,208,24 1,242).…”
Section: Experimental Approachesmentioning
confidence: 99%
“…The samples were stored at -70'C until analysis several weeks later. Previous studies showed that there is no loss of either receptor binding or adenylate cyclase activity under these circumstances compared with fresh tissue (19 (24).…”
Section: Introductionmentioning
confidence: 77%
“…The left ventricular free wall was then divided into the previously demarcated ischemic zone anteriorly and a normal posterior zone opposite to the area of ischemia. Each of these zones was then divided transmurally into two equal regions as previously described (19). These will be referred to as subendocardium and subepicardium throughout this manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation